0694 Concordance Between Self-reported And Objectively-assessed Sleep Duration Among African-american Adults: Findings From The Jackson Heart Sleep Study. (12th April 2019) - Jackson, Chandra L; Ward, Julia B; Johnson, Dayna A; Sims, Mario; Wilson, James; Redline, Susan
Abstract: Introduction: Most large-scale epidemiological studies rely on self-reported habitual sleep duration, and few have investigated the extent to which self-reported habitual sleep reflects average objectively-measured sleep duration, and whether associations vary by how subjective sleep duration is ascertained. Methods: Among African-American participants of the Jackson Heart Sleep Study, we investigated differences in self-reported sleep duration assessed by responses to two questions on self-assessed average sleep duration (SAASD) and self-assessed wake-bed time differences (SAWBD) on weekdays and weekends, and compared these responses to objective measures using 7-day wrist actigraphy. We employed linear regression models to assess bias between actigraphy-based and self-reported sleep duration, overall and separately for age, sex, educational attainment, insomnia symptoms, sleep apnea, and depressive symptoms. Results: Among 821 adults, mean age was 63.4 ± 10.7 years, 66.1% were women, and 74.4% had greater than a high school education. Mean weekday SAASD was significantly lower than SAWBD (6.4 ± 1.4 vs. 7.5 ± 1.7 hours, p<0.0001). Mean actigraphy-based total sleep time was 6.6 ± 1.2 hours, and actigraphy-based average time in bed was 7.6 ± 1.2 hours. Weekday SAASD and actigraphy-based total sleep time were modestly correlated (r=0.28, p<0.0001) and demonstrated slight agreement (κ=0.1848). SAASD underestimated weekday actigraphy-based total sleep time by approximately -30.7 (95% confidence intervals (CI): -36.5- -24.9) minutes. In contrast, SAWBD overestimated weekday sleep duration by approximately 45.1 (95% CI: 38.6-51.5) minutes compared to actigraphy-based total sleep time. Bias for weekend sleep was similar to weekday sleep. In subgroup analyses, SAASD significantly underestimated actigraphy-based measures among those with insomnia symptoms and, for weekend SAASD only, among those with less than a high school education and those aged 65+ years. We also observed a lower correlation (0.19 vs. 0.35, p<0.05) between SAASD and actigraphy-based sleep among participants with insomnia symptoms. Conclusion: Among African Americans, SAASD underestimated objectively-measured sleep while SAWBD overestimated objectively-measured sleep. Sleep measurement property differences should be considered when investigating disparities in sleep and evaluating its association with health outcomes. Support (If Any)